THE SPIRIT OF INDIVIDUALISM IN SHAKESPEARE’S HAMLET AND ALISHER NAVOI’S FARHOD VA SHIRIN - Ajikulova Ayajan Rinatovna, Khamitov Eldorbek Erkinovich (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
ABSTRACT This paper explores the manifestation of individualism in William Shakespeare’s Hamlet and Alisher Navoi’s Farhod va Shirin. Both authors, though rooted in different cultural and philosophical traditions—the Renaissance humanism of Europe and the Islamic humanism of Central Asia—depict protagonists who embody deep moral consciousness and personal responsibility. Hamlet’s existential reflections reveal a mind awakening to individual thought and moral freedom, while Farhod’s selfless devotion and intellectual independence demonstrate an Eastern vision of ethical individuality. Through their inner conflicts, both heroes question authority, tradition, and destiny, asserting the primacy of conscience and reason. The study argues that Shakespeare and Navoi, despite their divergent religious and cultural frameworks, share a universal belief in the dignity, moral agency, and self-awareness of the human being—making their works enduring testimonies to the spirit of individualism.